A comparative analysis of lesional skin, sentinel flap, and mucosal biopsies in assessing acute face transplant rejection - Kauke-Navarro, Martin; Huelsboemer, Lioba; Klimitz, Felix J.; Diatta, Fortunay; Knoedler, Leonard; Knoedler, Samuel; Crisler, William J.; Brown, Stav; Lian, Christine G.; Repetto, Federico; Clark, Rachael A.; Murphy, George F.; et al. (Frontiers in Immunology, 2025)
BackgroundFace transplant rejection is primarily monitored through skin biopsies, but mucosal tissue may detect immune rejection events missed by skin biopsies.MethodsWe retrospectively reviewed 47 paired mucosal and facial skin biopsies and 37 paired facial skin and sentinel flap biopsies from nine face transplant recipients. Rejection was graded using the 2007 Banff classification. Correlation, sensitivity, and specificity metrics were assessed.ResultsMucosa and facial skin rejection grades correlated strongly (r = 0.72, p < 0.0001), with mucosa showing a negative predictive value (NPV) of 0.85 for facial skin rejection. Mucosal biopsies identified rejection in 10 cases missed by facial skin biopsies. Sentinel skin biopsies had high correlation but an NPV of 0.76, missing 24% of rejection cases.ConclusionMucosal biopsies tend to capture the full spectrum of rejection, whereas skin biopsies alone may miss important rejection events occurring in the mucosa. Mucosal biopsies should be integrated into routine monitoring alongside skin biopsies, as they not only sensitively function as sentinel tissue but also provide critical insights into rejection activity that may otherwise go undetected. This dual approach could improve overall transplant surveillance. Inconsistencies in rejection patterns between the two tissues highlight the need for a reworked grading system.